Dinamika Psikologis Penderita Diabetes: Studi Kasus Perempuan Dewasa Madya Penderita Diabetes Melitus Tipe 2 - Setyani Alfinuha (Jurnal Psikologi, 2024)
Diabetes mellitus (DM) is a non-communicable chronic disease. DM disrupts the body's metabolism which is characterized by chronic hyperglycemic conditions with disorders of fat, carbohydrate and protein metabolism. DM is classified into two, namely type 1 and type 2. Most DM sufferers are classified as type 2. Type 2 DM sufferers need to undergo routine medical treatment such as taking medication regularly. Type 2 DM sufferers also need to carry out a series of other health maintenance activities and manage stress more adaptively so as not to worsen their DM condition. So far, most treatments for type 2 DM still focus on medical treatment such as taking medication. In fact, type 2 DM can also be worsened by depressed/stressful psychological conditions. Some type 2 DM sufferers experience stress, especially sufferers who are female and in the middle adulthood age category. This research uses a qualitative approach by conducting a case study on middle-aged women suffering from type 2 DM. The results of the research show that the psychological dynamics of DM sufferers can influence their disease. The dynamics of DM include views about the disease and its treatment, cognitive assessments and the emotions felt due to the disease suffered, as well as the pressure/stress felt.